In-situ Formation of Amorphous Co-Al-P Layer on CoAl Layered Double Hydroxide Nanoarray as Neutral Electrocatalysts for Hydrogen Evolution Reaction - Teng, Wanqing; Sun, Zhaomei; Xie, Junfeng; Wang, Ziqiang; Zheng, Xiangjiang; Tang, Bo (Frontiers in Chemistry, 2020)
Exploration of high-efficiency and inexpensive electrode catalysts is of vital importance for hydrogen evolution reaction (HER). In this communication, amorphous Co-Al-P layer is constructed on the surface of CoAl layered double hydroxide (CoAl-LDH) via in-situ wet phosphidation strategy. The core-shell CoAl-LDH@Co-Al-P on Ti mesh (CoAl-LDH@Co-Al-P/TM) as an active HER electrocatalyst demands an overpotential of 150 mV to achieve current density of 10 mA cm–2 at neutral pH. Moreover, CoAl-LDH@Co-Al-P/TM also exhibits good electrochemical stability and superior Faradic Efficiency with nearly 100%.